Pobreza rural e o Programa Bolsa Família: o caso dos beneficiários da comunidade de São João do Barro Preto - Júlio de Castilhos/RS - Mocelin, Cassia Engres (2011)
The Bolsa Família Program (BFP), established in 2003, is one of public policies to eradicate poverty in Brazil today, constitutes itself as the main tool to fight poverty from the federal government. Used as a determining variable to include the per capita income. The Family Grant Program is characterized by the direct transfer of conditional cash. Aims to ensure the human right to adequate food, promote food security and nutrition, contributing to the eradication of extreme poverty and the achievement of citizenship by the portion of the population most vulnerable to hunger. From this perspective, the research aimed to understand the impacts that the Family Grant Program promotes the living conditions of the beneficiary families in the community of São João do Barro Preto in the city of Julio de Castilhos/RS. The methodological procedures, the research drew on a literature review on the issues, and field research was conducted with the PBF beneficiary families through the application of a form. Subsequently, the data collected were analyzed quantitatively and qualitatively. Among the results, the study found that the Family Grant Program is a strategy of income redistribution, a conclusion also by other studies, and access and improve the living conditions of poor families. The study also allowed us to observe that the Bolsa Família Program represented an improvement in aspects of life of poor families in the community, such as women's empowerment, increased quantity and quality of food, access to consumer goods, higher purchasing power of families, increased in per capita income and family. The benefit of the PBF is the only form of permanent income that guarantees the survival of most families already living with the unemployment situation constantly, and with sporadic entry of other income arising from temporary jobs. On the other hand, the program still did not provide autonomy to the beneficiary families of the Community. Thus, expected to contribute to discussions about the Bolsa Familia, thinking about his advances, its potential and key obstacles to be tackled to achieve their goals. Key-words: Family Grant Program; Rural Poverty; Public